Glyphosate and the swirl : an agroindustrial chemical on the move - Adams, Vincanne, 1959- (Critical global health., 2023)
"Glyphosate and the Swirl is an ethnography of the agricultural chemical glyphosate (the active ingredient in the weed killer Roundup) that engages in the debate over the safety of the chemical in the scientific and activist communities. Vincanne Adams argues that glyphosate is an unstable and unreliable actor that has caused chemical harm despite the fact that it has radically changed our food production. Embracing speculation as integral to the scientific process, Adams theorizes the "swirl"-an unstable body that is constantly moving, concentrating and dissipating, gaining traction and losing it, and refusing to settle-to describe both the circulation of glyphosate in our environment and the evolution of public and scholarly knowledge about it."--